INJECTION MOULDING OF PLA (POLYLACTIC ACID) REINFORCED BACTERIAL CELLULOSE FIBER FROM NATA DE COCO BIOCOMPOSITES - Dini Cahyandari (Universitas Muhammadiyah Semarang, 2017)
For many applications, natural fibers provide reinforcement properties at lower cost, lower density, and higher strength and stiffness. The potential advantages of natural fiber have been well documented and are generallybased on environmental friendliness as well as health and safety factors. Most researches concentrate on naturalfibre/nondegradable polymer composites but research reports on natural/biodegradable polymer composites arerather limited. The performance of natural fiber including recycled newspaper fiber, bamboo and hemp fiber,nata de cassava etc, reinforced PLA composites has been investigated. Determined the mechanical propertiesof the PLA/jute fiber composites and showed that the tensile strength of composites was significantly higherthan that of PLA. But the elongation at break of the composites is still very low as about 2%. Cellulose is abiopolymer whose availability on earth is abundant, known as a major component in plants. But cellulose is alsoan extracellular microbial polymer. Cellulose bacteria is a specific product of primary metabolism. Cellulose issynthesized by bacteria derived from Acetobacter, Rhizobium, Agrobacterium, and Acetobacter generationSarcina. Effectively effective gram is acetobacter xylinum acetic acid bacteria. Cellulose bacteria has beenapplied as nata de coco, wound care products, and tissue engineering. In addition, bacterial cellulose also has thepotential to strengthen the polymer to form a nanocomposite Keywords: Bacterial, Nata De Coco